A 3DBER-S-EC process for simultaneous nitrogen and phosphorus removal from wastewater with low organic carbon content. (1st March 2018) - Hao, Ruixia; Zhou, Yanqing; Li, Jianbing; Wang, Jianchao
Abstract: A new process was proposed by integrating a three-dimensional biofilm electrode reactor with sulfur autotrophic denitrification and electrocoagulation within the same reactor. The results indicated that under the wastewater influent condition of NO3 − -N = 30 mg/L, COD = 45 mg/L, total phosphorus (TP) = 1.5 mg/L, hydraulic retention time (HRT) = 8 h, and I = 400 mA, the NO3 − -N and TP removal of the proposed process reached 89.8% and 83.0%, respectively. It was observed that the electrocoagulation process improved phosphorus removal, while the simultaneous existence of heterotrophic, hydrogen, sulfur and iron autotrophic denitrifying bacteria led to enhanced and stabilized nitrogen removal. The Sulfuritalea hydrogenivorans sk43H and Sulfuricella denitrificans skB26 were found as the dominant denitrifying bacteria in the electrocoagulation section and the section of biofilm electrode with sulfur filler, respectively. As compared to conventional technologies, the proposed new process can achieve simultaneous, stable and deep nitrogen and phosphorus removal from wastewater treatment plant effluent with low organic carbon content. Graphical abstract: Image 1 Highlights: A novel process was developed for simultaneous and deep denitrification and phosphorus removal. The NO3 − -N and TP removal reached 89.8% and 83.0% for influent C/N = 1.5 and TP = 1.5 mg/L. Sulfuritalea hydrogenivorans sk43H dominated in the electrocoagulation section of the process. Sulfuricella denitrificans skB26 dominated in the section of biofilm electrode with sulfur filler. Mechanisms of nitrogen and phosphorus removal in the novel process were analyzed.